2019
DOI: 10.14718/acp.2019.22.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Relación de estilos parentales disfuncionales, empatía y variables sociodemográficas en estudiantes de enfermería, medicina humana y psicología

Abstract: The objective of this study was to establish the relationship between dysfunctional parenting styles and empathy in Nursing, Human Medicine and Psychology students. The study's sample consisted of 599 students, from both genders, and from different cycles of their university studies. Their ages ranged between 21 and 25 years. To assess them, the Dysfunctional Parenting Styles Scale by Parker, et al. (1979) was used, previously adapted to Peruvian population. The participants were also evaluated with the Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…The outcomes of the present survey, on the other hand, differ from the results of a study by Williams et al that observed the empathy levels in nursing, undergraduate emergency health, and midwifery students and found that midwifery students had higher empathy levels than emergency health and nursing students [15]. Additionally, a study testing occupational therapy students' empathy at a Spanish institution revealed that these students demonstrated a high level of empathy [16].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The outcomes of the present survey, on the other hand, differ from the results of a study by Williams et al that observed the empathy levels in nursing, undergraduate emergency health, and midwifery students and found that midwifery students had higher empathy levels than emergency health and nursing students [15]. Additionally, a study testing occupational therapy students' empathy at a Spanish institution revealed that these students demonstrated a high level of empathy [16].…”
Section: Discussioncontrasting
confidence: 99%
“…To make the instrument more valid, it was presented to a panel of experts [16,17] (they had more than 10 years of practice) in the different fields related to the study title. Changes and modifications were made based on the experts' suggestions and recommendations to best fit to June 2024, Volume 22, Number 2 nursing sample.…”
Section: Validity Of the Questionnairementioning
confidence: 99%
“…Al mismo tiempo, Baumrind (1991) refiere que los tipos de crianza son el resultado de la unión entre la capacidad de afecto, autorregulación y exigencia de los padres. Matalinares-Calvet et al (2019) realizaron un estudio con una muestra estudiantes del área de salud e identificaron que los estilos parentales disfuncionales de ambos padres predominan de una forma medianamente significativa, resultando en que la mayoría de los evaluados han percibido que sus estilos de crianza se han basado en el abandono. Por su parte, Rodríguez y Céspedes (2019), trabajaron con una población similar, encontrando que en los padres predomina el tipo de crianza permisivo con un 48%, seguido por el estilo indulgente con 33%, autoritario 11% y finalmente el tipo negligente 8%.…”
Section: Introduciónunclassified
“…A pesar del cuerpo amplio de investigación respecto a las CAR, todavía no son concluyentes los datos sobre su etiología o mantenimiento. Por ejemplo, se ha sugerido que la percepción de las prácticas parentales, entendidas como aquellas creencias, actitudes y comportamientos que los padres ejercen sobre los hijos, con el propósito de influir, educar y orientar a los hijos para su desarrollo social y emocional, pueden tener un efecto negativo en diversas esferas de sus condescendientes (Matalinares-Calvet et al, 2019;Ruvalcaba-Romero, Gallegos-Guajardo, Caballo, & Villegas-Guinea, 2016). Es por ello que, cuando las dinámicas de interacción no son adecuadas podrían conducir al desarrollo de CAR, (Espinoza, Ochoa de Alda Martínez, & Ortego, 2007;Guttman & Laporte, 2002;Marmo, 2014;Sánchez, Villarreal, & Musitu, 2010).…”
Section: Introductionunclassified